Producción de saberes y transferencias culturales América Latina en contexto transregional - Birle, Peter; Carreras, Sandra; Paap, Iken; Schmidt-Welle, Friedhelm (Bibliotheca Ibero-Americana, 2023)
In recent decades, research focused on the production of knowledge and cultural transfers in Latin America in a transregional context has intensified. Its conception is largely based on the profile of the IAI, which is characterized by being not only a knowledge archive, but also a place of knowledge production and cultural and scientific exchange with and about Latin America. This volume brings together a series of articles by specialists in these subjects, most of whom worked at said institution as visiting researchers. It is the result, then, of an intense dialogue between them and the permanent researchers of the IAI. The volume critically discusses theoretical concepts, methodologies, and research on specific processes in the analysis of the production and circulation of knowledge, and cultural transfers in Latin America, from an intra- and trans-regional point of view.